The SWI/SNF complex subunit genes: Their functions, variations, and links to risk and survival outcomes in human cancers. (March 2018) - Savas, Sevtap; Skardasi, Georgia
Highlights: SWI/SNF genes are frequently mutated/altered in human cancers. Individual subunits may be mutated and implicated in more than one type of cancer. Multiple subunits may be mutated/altered in an individual cancer site. Expression levels of multiple SWI/SNF genes associate with survival times in TCGA datasets. Two BRM promoter indels associate with BRM expression and risk/prognosis of multiple cancers. Abstract: SWI/SNF is a multiprotein complex essential for regulation of eukaryotic gene expression. In this article, we review the function and characteristics of this complex and its subunits in cancer-related phenotypes. We also present and discuss the publically available survival analysis data for TCGA patient cohorts, revealing novel relationships between the expression levels of the SWI/SNF subunit genes and patient survival times in several cancers. Overall, multiple lines of research point to a wide-spread role for the SWI/SNF complex genes in human cancer susceptibility and patient survival times. Examples include the mutations in ARID1A with cancer-driving effects, associations of tumor SWI/SNF gene expression levels and patient survival times, and two BRM promoter region polymorphisms linked to risk or patient outcomes in multiple human cancers. These findings should motivate comprehensive studies in order to fully dissect these relationships and verify the potential clinical utility of the SWI/SNF genes in controlling cancer.